Case Report: Unusual High-Grade Diffuse Leptomeningeal Glioneuronal Tumor Mimicking Tuberculous Meningitis in a Child From an Endemic Region - Teh, Yong Guang; Azizan, Nornazirah; Mohd Naim, Nur Atifah; Ng, Chiak Yot; Wong, Ke Juin; Mohd Zaki, Faizah (Frontiers in Pediatrics, 2021)
Background: Diffuse leptomeningeal glioneuronal tumor (DL-GNT) is a new entity described in the 2016 World Health Organization (WHO) classification of brain tumors. While DL-GNT is predominantly an indolent tumor that affects young boys, high-grade DL-GNT is unusual and seldom reported in children. Case presentation: In this report, we describe the challenges and pitfalls associated with diagnosing this high-grade variant in a tuberculosis endemic region. We highlight the importance of identifying non-typical imaging findings - i.e. non-enhancing cystic lesions with high T2 signal along the leptomeningeal surface - that may expedite the diagnosis of this condition. Histopathologic correlations with MR spectroscopy findings are also discussed. Conclusion: We provide the first clinical imaging report of using MR spectroscopy to distinguish DL-GNT from tuberculosis with histopathologic correlation.